The Seven Parables in Matthew XIII - Gerhardsson, Birger (New Testament studies, 1972)
The section of gospel material often called ‘the parable chapter’ is handled very differently by the three synoptic evangelists (Mark iv. 1-34; Matt. xiii. 1-52; Luke viii. 4-18); an immediate and fundamental variation is apparent simply by counting the number of parables in each: Mark has three, Luke only one, Matthew as many as seven. This article on the Matthean version of the parable chapter begins by concentrating on its seven parables, for they belong together and their relationships promise to throw light on a number of problems.